2008
DOI: 10.1016/j.juro.2008.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Associations Between Nocturia and Sleep Disorders in Perimenopausal Women

Abstract: Purpose-To determine the associations between nocturia and sleep disorders in perimenopausal women.Material and Methods-100 women with nocturia were compared to 200 women without nocturia. The presence of obstructive sleep apnea, insomnia, anxiety and menopausal stage were assessed using validated questionnaires. Comorbidities associated with nocturia were determined by bivariable analysis and multivariable logistic regression.Results-Independent associations for nocturia were anxiety (OR 2.11, 95%CI 1.08,4.13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…22,27,28,35,36,76,[83][84][85][86] Data from the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial with 37 789 worldwide male participants showed that Asian men have the least risk of nocturia (OR = 0.7). 35 Conversely, a study by Mariappan et al including 293 male patients with LUTS, showed a higher prevalence of nocturia in Asian men than in Caucasian men (nocturia score was 2.90 vs 2.05, P < 0.001), which was attributable to a lower bladder capacity during the night in Asian men.…”
Section: Race/ethnicitymentioning
confidence: 99%
See 2 more Smart Citations
“…22,27,28,35,36,76,[83][84][85][86] Data from the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial with 37 789 worldwide male participants showed that Asian men have the least risk of nocturia (OR = 0.7). 35 Conversely, a study by Mariappan et al including 293 male patients with LUTS, showed a higher prevalence of nocturia in Asian men than in Caucasian men (nocturia score was 2.90 vs 2.05, P < 0.001), which was attributable to a lower bladder capacity during the night in Asian men.…”
Section: Race/ethnicitymentioning
confidence: 99%
“…84 Studies carried out in the USA generally reported that black races, in particular non-Hispanics or Africans, have a higher prevalence of nocturia than white races. 27,36,76,83 Kuo et al reported that aborigines and/or indigenous residents have more nocturia in eastern Taiwan. 85,86 However, it is unclear whether these differences in the prevalence of nocturia resulted from different races per se or from other divergent circumstances, such as socioeconomic and educational background.…”
Section: Race/ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] Further, survey studies have shown that the greater the number of nocturnal voids, the greater the self-described poor sleep, insomnia symptoms, and daytime sleepiness. [7][8][9][10][11][12][13][14][15] For those individuals who report nocturia as bothersome there is even a stronger correlation with disturbed sleep. 13,16 As noted, to date, no study of the relationship between sleep and nocturia has used objective measurements of sleep, nor have previous studies examined the relationship between sleep and nocturia prospectively, on a night-to-night basis.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…8 Parity and medical conditions, such as diabetes, obesity, and depression, are associated with prevalence and incidence of bladder symptoms. [9][10][11][12][13][14] Racial and gender differences in bladder symptoms, specifically symptoms of overactive bladder, such as incontinence or urgency, have also been reported. 4,11,15 The menopause transition is also associated with increased urinary complaints linked to the drastic reduction in endogenous estrogens, yet the literature remains unclear as to whether it is aging or reproductive stage that has the greater influence on bladder symptoms.…”
Section: Introductionmentioning
confidence: 99%